1999
DOI: 10.1080/108107399126841
|View full text |Cite
|
Sign up to set email alerts
|

Testing Different Formats for Communicating Colorectal Cancer Risk

Abstract: This study assessed the extent to which different formats of informing men and women age 50 and over of the risks of colorectal cancer (CRC) affected their perceptions of their absolute and comparative (self versus other) 10-year and lifetime risks; emotional reactions about getting CRC; and screening intentions. Forty-four men and 78 women received information about the absolute lifetime risk of getting CRC. In addition, participants either did or did not receive information about (1) lifetime risk of getting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Lipkus et al confirmed the importance of presenting risk information to those making decisions about health behaviors [27]. This research suggests that risk information can be presented to increase perceived risk without increasing worry, fear, or anxiety.…”
Section: Discussionmentioning
confidence: 77%
“…Lipkus et al confirmed the importance of presenting risk information to those making decisions about health behaviors [27]. This research suggests that risk information can be presented to increase perceived risk without increasing worry, fear, or anxiety.…”
Section: Discussionmentioning
confidence: 77%
“…Some evidence suggests that personalizing risk factors may increase individuals’ perceived disease risk [7476]. At baseline, our study population was divided between low and intermediate perceived risk, perhaps reflecting some optimistic bias given the high prevalence of reported family history [7779].…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence of these proposed influences is mixed. While Lipkus et al (1999) found no association between risk beliefs and these adequacy judgments, Dieckmann, Slovic, and Peters (2009) found that participants who rated risk information as more credible tended to have beliefs of greater risk.…”
Section: Theoretical Conceptsmentioning
confidence: 83%
“…Perceiving information as credible, trustworthy, and/or accurate is expected to foster message adoption and resulting changes in perceived risk and intentions to engage in protective behavior (Lipkus et al, 1999; Schapira, Nattinger, & McAuliffe, 2006). However, evidence of these proposed influences is mixed.…”
Section: Theoretical Conceptsmentioning
confidence: 99%